Transcriptome Analysis of Viable but Non-Culturable Brettanomyces bruxellensis Induced by Hop Bitter Acids - He, Yang; Zhao, Junfeng; Yin, Hua; Deng, Yuan (Frontiers in Microbiology, 2022)
The viable but non-culturable (VBNC) state has been studied in detail in bacteria. However, it has received much less attention in eukaryotic cells. The induction of a VBNC beer-spoilage yeast (Brettanomyces bruxellensis) by hop bitter acids with different concentrations and its recovery were studied in this work. B. bruxellensis cells were completely induced into the VBNC state by treatment of 250-mg/L hop bitter acids for 2 h. Addition of catalase at a concentration of 2000 U/plate on YPD agars enabled these VBNC cells to recover their culturability within 2 days. Moreover, the transcriptome profiling revealed that 267 and 197 genes were significantly changed upon VBNC state entry and resuscitation, respectively. The differentially expressed genes involved in the peroxisome activities, ABC transporter, organic acid metabolism, and TCA cycle were mainly downregulated in the VBNC cells. In contrast, the amino acid and carbohydrate metabolism, cell division, and DNA replication were promoted. This study supplies a theoretical basis for microbial risk assessment in the brewing industry.